Kombucha polysaccharide alleviates DSS-induced colitis in mice by modulating the gut microbiota and remodeling metabolism pathways - Ji, Zhong-Hao; Xie, Wen-Yin; Zhao, Pei-Sen; Ren, Wen-Zhi; Jin, Hong-Juan; Yuan, Bao (Frontiers in Microbiomes, 2024)
Ulcerative colitis (UC) is incurable, and rational dietary interventions are important in preventing UC. Kombucha is a fermented beverage that originated in China and has a variety of activities, including antioxidant, antibacterial and hypoglycemic activities. The aim of this study was to analyze the protective effect of Kombucha polysaccharide (KP) against UC and determine its mechanism of action. The results showed that KP intervention was effective in alleviating dextran sulfate sodium salt (DSS)-induced colitis symptoms and inhibiting DSS-induced inflammation and oxidative stress. Moreover, KP was able to reduce intestinal permeability, promote the expression of tight junction proteins, and help maintain thrush cell numbers and promote mucus secretion.The 16S rDNA results indicated that KP intervention increased the abundance of Rikenellaceae_RC9_gut_group and Clostridiales_unclassified. Untargeted metabolomics techniques revealed that KP can reverse DSS-induced disorders in intestinal metabolism. This study demonstrated that KP alleviated DSS-induced colitis by helping maintain intestinal barrier integrity, regulating the gut microbiota and remodeling metabolism pathways. The findings provide a theoretical basis for the application of KP as a dietary supplement for the prevention of UC.